Injecting single event upsets in a digital signal processor by means of direct memory access requests: a new method for generating bit flips - Ferreyra, P.A.; Marques, C.A.; Velazco, R.; Calvo, O. (2001 6th European Conference on Radiation and Its Effects on Components and Systems, 2001)
In this paper a novel approach for injecting Single Event Upsets, (SEU), by means of direct memory access, (DMA), mechanisms is presented. The system consists in a PC based control unit that generates DMA requests randomly in time to a board containing the processor under test, and a test unit. Experimentation performed on a digital signal processor intended to be used in a satellite project illustrates the potentialities of the proposed approach.